Moral courage in undergraduate nursing students: A literature review. Issue 1 (February 2017) - Bickhoff, Laurie; Sinclair, Peter M.; Levett-Jones, Tracy
Summary: Aim: The aim of this review was to explore factors which facilitate or inhibit undergraduate nursing students' willingness to demonstrate moral courage when confronted by poor patient care. Methods: Included papers were those that met the criteria of being qualitative research that explored undergraduate nursing students' depictions of situations where moral courage was or was not demonstrated during clinical placements, with a particular focus on situations that impacted or had the potential to impact the quality of patient care. Papers were reviewed using the Critical Appraisal Skills Programme Qualitative Research Checklist. The 15 papers included in the review were then thematically analysed. Findings: The literature reports, despite feeling a moral obligation to act, most nursing students lack the moral courage to intervene or speak up when faced with poor practice. While students may subsequently report the behaviour, at the time of the event, they often remain passive spectators and sometimes even active participants. The major themes identified in the literature were: just a student, don't rock the boat, fear of consequences, mentor–student relationship, and patient advocate identity. The literature also identified that nursing students suffer ongoing moral distress when they do not have the courage to confront poor practice. Conclusion: There is a need for further research to explore positive examples of how nursing students demonstrate moral courage when undertaking clinical placements. These narratives have the potential to influence future students' attitudes, values and behaviours by providing stimulus materials for teaching.